THE INFLUENCE OF MARKETING PUBLIC RELATION AND SERVICE QUALITY ON CORPORATE IMAGE THROUGH PUBLIC OPINION: STUDIES AT MANDIRI BANK - Vera Suciyati (ETIKONOMI, 2013)
This research aims to analyze the influence of marketing public relation and service quality at Bank Mandiri on corporate image through public. Convenience sampling method has been selected in order to obtain the data in this study. The analysis method that used was the path analysis. The research result had shown that: marketing public relation and service quality have significant influence simultaneously and partially on public opinion on the first structure equation. The second structure equation shows that: marketing public relation, service quality had significant influence simultaneously on corporate image. The service quality have not partially the quality of service have not influence significant partially on corporate, but variable marketing and public relation have  partially influential public opinion influence significant partially on corporate image.DOI: 10.15408/etk.v12i2.1916